2019
DOI: 10.1186/s13007-019-0487-8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding glycaemic control and current approaches for screening antidiabetic natural products from evidence-based medicinal plants

Abstract: Type 2 Diabetes Mellitus has reached epidemic proportions as a result of over-nutrition and increasingly sedentary lifestyles. Current therapies, although effective, are not without limitations. These limitations, the alarming increase in the prevalence of diabetes, and the soaring cost of managing diabetes and its complications underscores an urgent need for safer, more efficient and affordable alternative treatments. Over 1200 plant species are reported in ethnomedicine for treating diabetes and these repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 264 publications
(341 reference statements)
1
73
0
1
Order By: Relevance
“…Inclusion of higher dietary fibre and low glycaemic index foods in daily meals has been proved to reduce blood glucose levels, thereby reducing the risk of type 2 diabetes mellitus [ 9 ]. Indigenous edible plant extracts demonstrated anti-diabetic effects [ 10 ], such as insulin (diabetic drug), by executing the vital regulatory mechanism transporting the glucose uptake into skeletal muscle and adipose tissue by facilitating glucose transporter protein type-4 (GLUT4), playing a major role in the management of type 2 diabetes [ 11 ]. GLUT4 therefore plays a vital role in glucose homeostasis of skeletal muscle cells and the removal of glucose from blood circulation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of higher dietary fibre and low glycaemic index foods in daily meals has been proved to reduce blood glucose levels, thereby reducing the risk of type 2 diabetes mellitus [ 9 ]. Indigenous edible plant extracts demonstrated anti-diabetic effects [ 10 ], such as insulin (diabetic drug), by executing the vital regulatory mechanism transporting the glucose uptake into skeletal muscle and adipose tissue by facilitating glucose transporter protein type-4 (GLUT4), playing a major role in the management of type 2 diabetes [ 11 ]. GLUT4 therefore plays a vital role in glucose homeostasis of skeletal muscle cells and the removal of glucose from blood circulation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In same context, it is illustrated that the phytocompounds have the ability to inhibit speci c enzymes by binding to the active site within the enzyme molecule or a related mode of action [56,57]. Ideal inhibitors have a low molecular weight that can reduce or completely inhibit enzyme activity at low concentrations [55].…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical analysis of the samples was used for the identification of constituents, using procedures previously described [9]. The presence of alkaloids was tested by Mayer, Dragendorff, and Bouchardat's reagent; phenolics and tannin were tested with 2% FeCl 2 and 1% gelatine in 10% NaCl; the flavonoids were tested with a Shinoda test and alkaline reagent; triterpenoids were tested with the Liebermann-Burchard test; steroids were tested with a Salkowski test; and saponins were tested by a foam test with distilled water.…”
Section: Preliminary Phytochemical Investigationmentioning
confidence: 99%
“…Medicinal plants continue to contribute significantly to developing modern prescription drugs by providing lead compounds upon which the synthesis of new drugs can be made. Therefore, the hypoglycemic activity of a number of plant extracts has been evaluated and confirmed in animal models [8][9][10]. Many recent studies have revealed that plant-based formulations can contribute to a better management of diabetes, as certain phytochemicals exert antioxidant, anti-inflammatory, and glucose-lowering effects [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%